2017
DOI: 10.31219/osf.io/tm3kb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of ISO 9001 Certification on the Projects' Success of Large-scale (AAA) Construction Firms in the Philippines

Abstract: The general purpose of this study is to investigate the effects of ISO 9001 certification on project success, and its main criteria into large-scale construction companies in Metro Manila, Philippines. For this aim, the research was conducted an in-depth literature review for identifying the main variables first. Subsequently, a survey questionnaire was designed, and distributed randomly among 67 managers working in ISO 9001:2008- certified projects of large-scale construction firms. Then the descriptive and i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…From Table 1, it can be observed that these empirical studies were carried out between 2002 and 2017. The reason that this research was selected and focused only on empirical studies after 2000 because ISO was upgraded ISO 9001 in 2000, from a quality assurance tool to an effective quality management technique with a tested structure based on PDCA cycle, which gives possibility to this standard in improving the performance of the organizations continuously [21], [8]. Furthermore, most of the studies were accomplished within manufacturing sector in different countries.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…From Table 1, it can be observed that these empirical studies were carried out between 2002 and 2017. The reason that this research was selected and focused only on empirical studies after 2000 because ISO was upgraded ISO 9001 in 2000, from a quality assurance tool to an effective quality management technique with a tested structure based on PDCA cycle, which gives possibility to this standard in improving the performance of the organizations continuously [21], [8]. Furthermore, most of the studies were accomplished within manufacturing sector in different countries.…”
Section: Resultsmentioning
confidence: 99%
“…This result is also consistent with view of Han et al [4], who noted that it is not surprising to find from the studies that ISO 9001 standard efforts do not affect customer issues directly, because an organization which has ISO 9001, is often expected to promote customer's satisfaction and consistently provide product or service that meets customer and regulatory requirements [14], but in fact, it does not guarantee that ISO 9001 always improves quality performance of the organizations for satisfying customers [24]. Similarly, Neyestani & Juanzon [21] stated that the reasons of the majority of the construction companies for being an ISO 9001-certified firm are to become eligible in tendering of government and international projects, and also achieving its competitive advantages as a marketing tool. Thus, they often neglect to use ISO 9001 properly with the aim of obtaining performance excellence and its multiple advantages.…”
Section: Impact Of Iso 9001 On Customer Perspectivementioning
confidence: 99%
See 3 more Smart Citations